Estudo dos efeitos farmacológicos do (-)-α-bisabolol em modelos animais de nocicepção, inflamação e úlcera gástrica em camundongos - Rocha, Nayrton Flávio Moura (2009)
(-)-a-bisabolol, a sesquiterpenic álcool, is commonly obtained from Matricaria chamomilla and from species of Vanillosmopsis, it was tested in animal standardized models of nociception, inflamation and gastric ulcer in mice. In this assays, (-)-a-bisabolol was used in the doses of 25 and 50 mg/Kg in the models of nociception and 100 and 200 mg/Kg in the models of inflamatiom and gastric ulcers, administered by via oral. (-)-a-bisabolol demonstrated to have an antinociceptive activity in the models of visceral nociception induced by intraperitoneal acetic acid and in the second phase of the test nociception was induced by intraplantar administration of formaline. (-)-a-bisabolol did not demonstrate activity in the thermal nociception model of hot plate. These findings suggests that the antinociceptive action of (-)-a-bisabolol is not linked to central mechanisms and may be related with pre inflamatory process. In the models of paw oedema induced by carragenine and dextran the animals treated with (-)-a-bisabolol showed smaller oedemas as compared to animals treated only with the vehicle. (-)-a-bisabolol was capable to reduce the paw oedemas induced by 5- HT, but not the oedema induced by histamine, so it could relate the antiinflamatory activity of (-)-a-bisabolol to the interference in the action/liberation or in the systesis/metabolism of 5- HT. (-)-a-bisabolol demostrated having gastroprotective activity in the absolute ethanol and indomethacin-induced gastric lesions. The mechanism of this action was pharmacologicaly tested, doing pre-treatments with L-NAME, Glibenclamide and Indomethacin. These experiments demonstrated that tha gastroprotective action of (-)-a-bisabolol seems not to be involved the nitric oxide, potassium channels ATP-dependents or the sysntesis of prostaglandines. By the way, the quantification of GSH in the gastric tissues of not lesioned animals e lesionated by ethanol or indomethacin showed that the treatment with (-)-a- bisabolol atenuate the decrease of GSH associated with the lesive agents, but it did not increase its levels in the animals that not recieve ethanol or indomethacin. This way (-)-a- bisabolol increase the disponibility of GSH in the gastric tissue, having in vivo antioxidant activity, that allows us to associate this finding to its gastroprotective action.